CAMPO MINADO/MINEFIELD: War, Affect and Vulnerability - A Spectacle of Intimate Power - Sosa, Cecilia (2017)
This essay reflects on the different spectatorial, political, cultural, affective and bodily experiences of attending Lola Arias´s MINEFIELD/CAMPO MINADO, both at the Royal Court in London and at a university auditorium in Buenos Aires. Drawing upon the 1982 Malvinas/Falklands War, the Argentine internationally recognized director´s production featured six former soldiers who used to be enemies on the battlefield telling real stories about the conflict. Although there was almost nothing that could be called traditional theatre onstage, the production received standing ovations on both sides of the Atlantic. But what was applauded at the end of each performance? The audiences´ reactions, including my own, were very different at the two venues. I argue that Arias´s production hinged upon a high-risk, highly exposed public encounter that envisioned a change of perspectives, not only for the ex-soldiers involved but also for the spectators. Rather than staging veterans as war heroes, Arias´s social experiment exposed both teams on a common ground of vulnerability. MINEFIELD constructed a spectacle of intimate power that delineated a naked form of transnational citizenship.